Die Thun-Hohenstein'sche Universitätsreformen 1849-1860 Konzeption - Umsetzung - Nachwirkungen - Aichner, Christof (2017)
The book gathers 14 articles on the reforms of the Austrian University system from 1848 to 1860 named after Leo Thun Hohenstein. The reforms mark a turning point in the history of the Austrian educational landscape. The book provides new perspectives on the work of Leo Thun-Hohenstein, using to date unknown sources and new approaches.